Pengembangan Usaha Inovasi Produk Udang “Khairun Shrimp” Hasil Budidaya - Munaeni, Waode; Iis Hamsir Ayub Wahab; Nursanti Abdullah; Disnawati (Politeknik Piksi Ganesha Indonesia, 2026)
This entrepreneurship-based community service program focuses on the cultivation and commercialization of Litopenaeus vannamei shrimp in coastal areas. The implementation method begins with the stocking of vannamei shrimp postlarvae for grow-out, followed by regular monitoring of growth performance through periodic shrimp sampling. Once the shrimp reach marketable size, the harvesting process is conducted. The harvested shrimp are subsequently processed and properly packaged and branded under the name “Khairun Shrimp” to enhance product value and competitiveness. Marketing strategies are implemented through sales at several exhibitions, which aim not only to market the product but also to increase brand visibility. The peak of the promotional activities was participation in an exhibition attended directly by the Minister of Education, Culture, Research, and Technology and the Rector of Khairun University (Unkhair). The success of this exhibition provided significant impacts, including product validation, increased consumer trust, and expansion of marketing networks. Overall, this program successfully demonstrates a sustainable entrepreneurship model that integrates production, packaging, branding, and marketing aspects, serving as a potential reference for the development of micro-enterprises in the marine and fisheries sector.